Prototipe Sistem Manajemen Tabungan Siswa Berbasis Web dengan Notifikasi Real-Time (Studi Kasus: SDN Pondok Jagung 3) - Azis Firdaus; Maulana Muhamad Sulaiman (Jurnal Riset Multidisiplin Edukasi, 2025)
The student savings program in elementary schools plays an important role in fostering early financial management habits. However, manual recording methods often cause problems such as delays, errors, and limited transparency for parents. This study aims to develop a prototype of a web-based student savings management system equipped with real-time notifications to improve efficiency and transparency. The research employed the prototype method, including needs identification, design, implementation, and testing. The system was built using PHP and MySQL, supported by the Telegram Bot API to deliver transaction notifications to parents. Black box testing confirmed that all functions operated correctly. Furthermore, a questionnaire distributed to 20 respondents resulted in an average score of 80% for the appearance variable and 80.4% for the effectiveness variable, both categorized as “Very Good.” These findings demonstrate that the proposed system successfully enhances the speed, accuracy, and transparency of savings management while providing convenience for parents to monitor student transactions in real time.